Computer Systems : A Programmer's Perspective - Bryant, Randal E. and O'Hallaron, David R. 1955- (Noida, India Pearson Education, 2017)
This book is for programmers who want to write faster and more reliable programs. By learning how programs are mapped onto the system and executed, readers will better understand why programs behave the way they do and how inefficiencies arise ... Topics include: data representations, machine-level representations of C programs, processor architecture, program optimization, memory hierarchy, linking, exceptional control flow, virtual memory and memory management, system-level I/O, network programming, and concurrent programming. The coverage focuses on how these areas affect application and system programmers ... The book is based on Intel-compatible (IA32) machines executing C programs on Unix or related operating systems such as Linux. Some familiarity with C or C++ is assumed, although hints are included to help readers making the transition from Java to C
Include Appendix and Index
Keywords: User interfaces (Computer systems) -- Computers -- Telecommunication